Prisms for timing better: A review on application of prism adaptation on temporal domain. (October 2019) - Anelli, Filomena; Frassinetti, Francesca
Abstract: The possibility to induce a transient modulation of visuo-spatial attention boosted so far the implementation of the prism adaptation in a variety of domains. This sensorimotor technique has been adopted to investigate the neural plasticity in neurologically healthy individuals, as well as to ameliorate deficit of visuo-spatial attention (which characterizes neglect patients' performance). We review here evidence about a new promising application of prisms in exploring how the human brain represents the subjective time flow on a spatially oriented "mental time line". Converging observations in healthy individuals suggest that altering spatial attention processing via prism adaptation can influence the spatial representation of time. These modulatory effects are generalizable to different aspects of time, such as the abilities to estimate time duration and to mentally travel in time. Furthermore, data from brain damaged patients, with a special focus on right brain-damaged patients with neglect, indicate that prismatic procedure ameliorates temporal deficits, hence paving the way to novel clinical applications. We conclude by discussing the possible cognitive mechanisms and neural circuits of the prism adaptation effects on time.